2010
DOI: 10.1016/j.ophtha.2009.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Descemet's Stripping Automated Endothelial Keratoplasty Outcomes Compared with Penetrating Keratoplasty from the Cornea Donor Study

Abstract: Purpose-To assess outcomes 1 year after Descemet's stripping automated endothelial keratoplasty (DSAEK) in comparison with penetrating keratoplasty (PKP) from the Specular Microscopy Ancillary Study (SMAS) of the Cornea Donor Study. Design-Multicenter, prospective, nonrandomized clinical trial.Participants-A total of 173 subjects undergoing DSAEK for a moderate risk condition (principally Fuchs' dystrophy or pseudophakic/aphakic corneal edema) compared with 410 subjects undergoing PKP from the SMAS who had cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
147
3
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(167 citation statements)
references
References 27 publications
7
147
3
3
Order By: Relevance
“…[46][47]50,76,97,[103][104][105]123 Tourtas et al found that central corneal thickness reduced from 652+/-92 microns to 517+/-45 microns after DMEK and from 698+/-137 microns to 618+/-66 microns after DSAEK. 123 This difference in thickness is one explanation for the improved visual outcomes.…”
Section: Reducing Graft Thicknessmentioning
confidence: 99%
“…[46][47]50,76,97,[103][104][105]123 Tourtas et al found that central corneal thickness reduced from 652+/-92 microns to 517+/-45 microns after DMEK and from 698+/-137 microns to 618+/-66 microns after DSAEK. 123 This difference in thickness is one explanation for the improved visual outcomes.…”
Section: Reducing Graft Thicknessmentioning
confidence: 99%
“…As less donor tissue is needed in DSAEK and is implanted in an immunological favourable environment with no need of corneal sutures, it has been speculated that the risk of graft rejection and rejection-related failures is lower after DSAEK than after PK. Preparation, insertion and manipulation of the posterior lamellar transplant possibly increase the probability of endothelial cell loss after DSAEK, which may induce primary failure, or endothelial decompensation over time (Price et al 2010;Yoeruek et al 2014). Several previous studies have described and compared the risk of graft rejection and failure after DSAEK and PK (Beckingsale et al 2006;Allan et al 2007;Price et al 2009;Anshu et al 2012;Wu et al 2012;Hjortdal et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2 Corneal transplantation using post-mortem donor tissue is the only effective treatment for FED. 5 The prevalence of FED varies markedly across the world. It affects B4% of the USA population over the age of 40 years, 6 but is less frequent in Asian 7 and Middle-Eastern populations.…”
Section: Introductionmentioning
confidence: 99%